Розробка оптимальної компоновки горизонтального трьохшпиндельного верстата для комплексної обробки сферичних поверхонь з дослідженням властивостей змінних безвольфрамових тришарових ріжучих пластин різців - Іванов, Ілля Ярославович; Ivanov, Illia (ЦНТУ, 2025)
Розробка оптимальної компоновки та основних вузлів горизонтального трьохшпиндельного верстата для комплексної обробки сферичних поверхонь та дослідження властивостей змінних безвольфрамових тришарових ріжучих пластин різців, що використовуються для обробки сферичних поверхонь. Метою роботи є розробка оптимальної компоновки та основних вузлів горизонтального трьохшпиндельного верстата для комплексної обробки сферичних поверхонь та дослідження властивостей змінних безвольфрамових тришарових ріжучих пластин різців, що використовуються для обробки сферичних поверхонь. Для досягнення мети дослідження було вирішено такі задачі: обрано верстат, який повинен стати базою для розробки проектованого верстата; розроблено оптимальний варіант компоновки проектованого верстата; досліджено властивості змінних безвольфрамових тришарових ріжучих пластин; розроблено технологічний процес обробки верхньої кулькової опори для проектованого верстата; розроблено спеціальні основні вузли проектованого верстата та їх основні характеристики; виконано техніко-економічне обґрунтування доцільності використання горизонтального трьохшпиндельного верстата для комплексної обробки сферичних поверхонь. The development of an advanced machine tool for machining ball joints used in the front suspension system is an important task. A vehicle with a damaged front suspension-whose key components include ball joints-poses a significant safety risk during operation. Typically, this hazard can be eliminated by replacing the ball joints in the vehicle’s front suspension. To ensure that companies and manufacturers have adequate supplies of spare parts, there is a need to design and produce machine tools intended for machining ball joints. The aim of the work is to develop an optimal layout and the main units of a horizontal three-spindle machine tool for comprehensive machining of spherical surfaces, as well as to study the properties of replaceable tungsten-free three-layer cutting inserts used for machining spherical surfaces. To achieve this goal, the following tasks were completed: a machine tool was selected as a base for designing the new machine; an optimal layout of the designed machine tool was developed; the properties of replaceable tungsten-free three-layer cutting inserts were examined; a technological process for machining an upper ball joint for the designed machine was developed; special main units of the designed machine and their key characteristics were created; a techno-economic justification for the feasibility of using a horizontal three-spindle machine tool for comprehensive machining of spherical surfaces was carried out.
Development of the optimal layout of a horizontal three-spindle machine for complex machining of spherical surfaces with research into the properties of replaceable tungsten-freethree-layer cutting inserts for cutters
Keywords: сферичні поверхні; безвольфрамові тришарові ріжучі пластини; трьохшпиндельний верстат; кулькові опори; spherical surfaces; tungsten-free three-layer cutting inserts; three-spindle machine tool; ball joints